Development of Learning Model for Squat-style Long-jump Basic Technique Based on Biomechanics with a Game - Defliyanto Defliyanto; Moch Asmawi; Ramdan Pelana; Yarmani Yarmani (PendIPA Journal of Science Education, 2020)
The aims of this development research were to produce a learning model for basic technique of squat-style long-jump based on biomechanics with the game for junior high school students and to know the effectiveness, efficiency and attractiveness against learning model. This research used Deff model adopted from Research & Development by Borg and Gall. The subject used was junior high school students which consists of 45 students. The instruments used were need analysis, expert’s evaluation, small and large group test. Effectiveness test was to know junior high school students’ jump skill level before being given biomechanic treatment. The Pre-test obtained from the students’ jump result was about 540, and Post-test was about 812. The conducted t-test between the experiment group and the control group obtained was t = 10.152 and in the n-gain score test between the experiment group (biomechanic treatment) obtained by 76% (effective) and the control group obtained by 43.40% (less effective). Therefore, this game model is effective in increasing students’ jump learning. According to the result, it could be inferred that: (1) this model can be developed and applied in physical education, (2) the model proved that there are significant difference in pre-test and post-test between the experiment group (biomechanic treatment) and the control group after the treatment model, based on N-gain test.